Plasma and aqueous levels of alarin and adipsin in patients with and without diabetic retinopathy - Gul, Fatih Cem; Kobat, Sabiha Gungor; Celik, Fatih; Aydin, Suleyman; Akkoc, Ramazan Fazil (Bmc, 2022)
Backround Diabetic retinopathy is a disease seen with microvascular complications as a result of hyperglycemia and insulin resistance. Alarin and Adipsin are molecules with a role in energy and glucose metabolism. The aim of this study was to determine plasma and aqueous levels of Alarin and Adipsin in patients with and without diabetic retinopathy to evaluate their potential roles in diabetic retinopathy. Methods The study included one eye from each of 20 cataract patients without diabetes (C), 20 cataract patients with diabetes and without diabetic retinopathy (DM + C), and 20 cataract patients with diabetes and diabetic retinopathy (DR + C). Plasma and aqueous humour samples were taken from all patients during the cataract operation. Alarin and Adipsin levels were examined with the enzyme-linked immunosorbent assay (ELISA) method. Results Both plasma and aqueous Alarin levels were significantly higher in the patients with diabetic retinopathy than in the control group (p < 0.001, p = 0.006). Adipsin levels were found to be significantly higher in plasma in the control group than in the DR + C group and significantly higher in aqueous in the DR + C group than in the control group (p < 0.001, p < 0.001). Conclusion These findings suggest that Alarin and Adipsin may play important role in diabetic retinopathy.
Keywords: Diabetic retinopathy; Alarin; Adipsin; Plasma; Aqueous